The Hidden Savior - Samah Abd Al-Rahman; Ameera Shobaki (My University, 2024)
With the increase in suffocation incidents in cars, especially among children, there has become an urgent need for technological solutions capable of detecting risks and mitigating their effects effectively. Our “Invisible Rescuer” project aims to prevent suffocation and detect other dangers such as fires and accidents caused by children while playing. In the car, they start it. This is where our project comes into play, as it allows the car owner to stop it remotely. Our project also provides continuous alerts for immediate responses. In short, we have developed a comprehensive safety system that addresses the safety of cars and people, especially children. The system uses Co2 sensors to monitor oxygen levels throughout the car. When oxygen levels are detected below safe limits when there are passengers in the car, an internal alarm is activated and a notification is sent to the car owner, and the system automatically opens the windows to let in fresh air. Furthermore, the system includes smoke and flame detection sensors. When detected, an SMS message is sent to the fire services and the car’s location is sent using the Global Positioning System. One of the features of “The Hidden Savior” project is that if there are children in the car and they start it, the car can be stopped through the application. In addition, if the car is locked with the key inside, the owner can unlock it through the mobile application after verifying the identity of the car owner by entering a secure code that interacts with the door opening system. This safety system aims to prevent suffocation and accidents and flexibly deal with fire situations in cars, which greatly enhances safety. By leveraging advanced sensor technologies and wireless communications capabilities, they play a critical role in saving lives and mitigating risks associated with suffocation and fires inside cars.